Second-language phoneme learning positively relates to voice recognition abilities in the native language: Evidence from behavior and brain potentials - Díaz, Begoña; Cordero, Gaël; Hoogendoorn, Joyce; Sebastian-Galles, Nuria (Frontiers in Psychology, 2022)
Previous studies suggest a relationship between second-language learning and voice recognition processes, but the nature of such relation remains poorly understood. The present study investigates whether phoneme learning relates to voice recognition. A group of bilinguals that varied in their discrimination of a second-language phoneme contrast participated in this study. We assessed participants’ voice recognition skills in their native language at the behavioral and brain electrophysiological levels during a voice-avatar learning paradigm. Second-language phoneme discrimination positively correlated with behavioral and brain measures of voice recognition. At the electrophysiological level, correlations were present at two time windows and are interpreted within the dual-process model of recognition memory. The results are relevant to understanding the processes involved in language learning as they show a common variability for second-language phoneme and voice recognition processes.